Physiology of a Hybrid Pathway for Nicotine Catabolism in Bacteria - Huang, Haiyan; Shang, Jinmeng; Wang, Shuning (Frontiers in Microbiology, 2020)
Nicotine is a major N-heterocyclic aromatic alkaloid produced in tobacco plants and the main toxic chemical in tobacco waste. Due to its complex physiological effects and toxicity, it has become a concern both in terms of public health and the environment. A number of bacteria belonging to the genera Arthrobacter and Pseudomonas can degrade nicotine via the pyridine and pyrrollidine pathways. Recently, a novel hybrid of the pyridine and pyrrolidine pathways (also known as the VPP pathway) was found in the Rhizobiale group bacteria Agrobacterium tumefaciens S33, Shinella sp. HZN7 and Ochrobactrum sp. SJY1 as well as in other group bacteria. The special mosaic pathway has attracted much attention from microbiologists in terms of the study of their molecular and biochemical mechanisms. This will benefit the development of new biotechnologies in terms of the use of nicotine, the enzymes involved in its catabolism, and the microorganisms capable of degrading the alkaloid. In this pathway, some metabolites are hydroxylated in the pyridine ring or modified in the side chain with active groups, which can be used as precursors for the synthesis of some important compounds in the pharmaceutical and agricultural industries. Moreover, some enzymes may be used for industrial biocatalysis to transform pyridine derivatives into desired chemicals. Here, we review the molecular and biochemical basis of the hybrid nicotine-degrading pathway and discuss the electron transport in its oxidative degradation for energy conservation and bacterial growth.